Language Development Over the Lifespan - Cynthia S. Wiseman (Working Papers in Applied Linguistics and TESOL, 2015)
Language Development over the Lifespan, compiled by Kees de Bot and Robert W. Schrauf, is a collection of articles that explore language development—both language acquisition and language attrition—from a lifespan perspective. This volume of articles was, first of all, intended as a reference resource for research on language development and the aging process and as a text for MA courses in applied linguistics/bilingualism programs. More importantly, this book establishes a new and exciting perspective on language acquisition by considering developmental language phenomena, that is, “developmental” changes in language that occur over the span of a lifetime. This volume thus opens up new windows to research language acquisition from a developmental perspective. Language development becomes a function of the interaction of timescales both within the lifespan of the individual and at a larger “biocultural” (i.e., historical) level of language development. Historical events like the adoption of an official language by a government, for example, generate changes in language use at a macro-level, which in turn produce “cohort effects” that affect language development within the individual. A key concept to this lifespan perspective is that language is a dynamic system involving multiple components and subsystems. This book provides a comprehensive overview of the impact of cognitive and psychological factors, as well as social and cultural factors like the role of life events in the dynamic development of language.